2013
DOI: 10.1111/acer.12115
|View full text |Cite
|
Sign up to set email alerts
|

Comments and Reflections on Ethics in Screening for Biomarkers of Prenatal Alcohol Exposure

Abstract: Early identification of and intervention for fetal alcohol spectrum disorder (FASD) has been shown to optimize outcomes for affected individuals. Detecting biomarkers of prenatal alcohol exposure (PAE) in neonates may assist in the identification of children at risk of FASD enabling targeted early interventions. Despite these potential benefits, complicated ethical issues arise in screening for biomarkers of PAE and these must be addressed prior to the implementation of screening programs. Here, we identify an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…93 Early diagnosis and intervention are associated with improved outcomes for children with FASD, 43 and thus it could be argued that a test with high sensitivity could be favored over specificity in this context because it may facilitate appropriate monitoring and follow-up among children with positive PAE screens. However, PAE is a highly emotive topic, and false-positive errors may lead to stigmatization and unnecessary burden on health care resources, and may even be used in legal proceedings against mothers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…93 Early diagnosis and intervention are associated with improved outcomes for children with FASD, 43 and thus it could be argued that a test with high sensitivity could be favored over specificity in this context because it may facilitate appropriate monitoring and follow-up among children with positive PAE screens. However, PAE is a highly emotive topic, and false-positive errors may lead to stigmatization and unnecessary burden on health care resources, and may even be used in legal proceedings against mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Given the implications of both types of diagnostic error, various authors have suggested that both high sensitivity and specificity are a prerequisite for the introduction of PAE screening. 55,93,96 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being proactive in discussions of alcohol use with male and non-pregnant female patients of all backgrounds is also important to reducing the many potential harms of alcohol consumption, and this universal approach may reduce feelings of being targeted or stigmatized. 49 …”
Section: How To Communicate Prevention Messages Given the Potential Fmentioning
confidence: 99%
“…The ethical and legal issues raised by diagnosing FASD on the basis of self-reported maternal drinking during pregnancy also apply to the use of putative biomarkers, such as meconium tests, for detecting prenatal exposure to alcohol in the fetus or newborn baby [55,56]. These tests may establish if a child has been exposed to alcohol in utero more accurately than women's self-reported drinking but they raise similar considerations over the comparative 'rights' of the mother and her child.…”
Section: Social and Ethical Implications Of Diagnosing Fasdmentioning
confidence: 99%